The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1540/jsmr.43.43
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of abnormal intestinal motility in inflammatory bowel disease: how smooth muscle contraction is reduced?

Abstract: Intestinal inflammation alters the contractile activity of intestinal smooth muscle. Motility disorders of the gastrointestinal tract are clinically important symptoms, because they are often associated with severe interstitial inflammation. In addition, the motility disorders secondarily induce abnormal growth of the intestinal flora, and the resulting disturbance of this flora aggravates the pathogenesis of mucosal inflammation. This in turn aggravates the intestinal dysmotility; i.e., it is an inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 66 publications
1
85
0
1
Order By: Relevance
“…Although there is ample evidence from animal experiments that gastrointestinal motility including gastric emptying is altered by intestinal inflammation (43), pathomechanisms causing delayed gastric emptying in inflammatory diseases of the human distal gastrointestinal tract have not been investigated, so far. Specifically in CD, duodenal obstruction might impede gastric emptying; however, duodenal obstruction is a rare condition, none of our patients had evidence of upper gastrointestinal obstruction, and delayed gastric emptying has been demonstrated in patients with nonobstructive CD before (2).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is ample evidence from animal experiments that gastrointestinal motility including gastric emptying is altered by intestinal inflammation (43), pathomechanisms causing delayed gastric emptying in inflammatory diseases of the human distal gastrointestinal tract have not been investigated, so far. Specifically in CD, duodenal obstruction might impede gastric emptying; however, duodenal obstruction is a rare condition, none of our patients had evidence of upper gastrointestinal obstruction, and delayed gastric emptying has been demonstrated in patients with nonobstructive CD before (2).…”
Section: Discussionmentioning
confidence: 99%
“…activity of various signaling molecules that regulate smooth muscle contraction and relaxation (Akiho et al, 2002;Shi et al, 2003;Cao et al, 2004;Jin et al, 2004;Salinthone et al, 2004;Singer et al, 2004;Shi and Sarna, 2005;Zhao et al, 2005Zhao et al, , 2006Khan and Collins, 2006;Ohama et al, 2007;Ihara et al, 2012;Shea-Donohue et al, 2012;Yang et al, 2013). Previous studies have identified that signaling pathways that mediate initial and sustained contraction in intestinal longitudinal muscle are distinct from those in circular muscle (Grider and Makhlouf, 1988;Murthy, 2006).…”
Section: Regulation Of Cgmp Levels By Cytokinesmentioning
confidence: 99%
“…14 Although many studies have been conducted to investigate digestive tract motility using various animal models, [15][16][17][18][19][20][21][22][23][24] few studies have been conducted using IL-10 −/− mice. Accordingly, this study was conducted to investigate changes in colonic contractility in IL-10 −/− mice and the possible mechanisms of these changes.…”
mentioning
confidence: 99%